Influence of Gender and Age on the Peripheral Immune Response in Stroke. Issue 4 (July 2016) - Ross, Amy Miner; Lee, Christopher S.; Lutsep, Helmi
Abstract : Background: Women and men have unique stroke risk factors and can experience different poststroke infections. Objective: The aim of this study is to determine the influence of gender, age, and risk factors on the peripheral immune response in stroke/transient ischemic attack (TIA). Method: A total of 192 adult acute stroke/TIA cases were analyzed for age, gender, risk factors for stroke/TIA, and white blood cell with differential count. χ 2 Test and analysis of variance were conducted to test for differences between genders and age groups related to stroke risk factors and the immune response. Growth modeling was used to test for trended differences in the immune response. Results: Women were 4 years older than men; fewer women had strokes in the younger age group (<79 years) and more men currently smoked. Trended lymphocyte percentages for the young and old (slope, P = .04; pattern, P = .02) and admission monocyte percentages by gender were significantly different ( P = .01). Conclusions: Age influenced trended lymphocyte numbers and gender influenced monocyte percentage on admission.